2015
DOI: 10.1039/c5ra06095h
|View full text |Cite
|
Sign up to set email alerts
|

Parallel synthesis and biological evolution of quinic acid derivatives as immuno-suppressing agents against T-cell receptors

Abstract: A parallel synthesis of quinic acid derivatives is explored and their biological evolution against T-cells is studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In a further study, a series of cynarin derivatives was evaluated using this method, and results showed that one of the derivatives, Cyn-1324, reached a blocking effect of 31%. 96 In another study, the authors detailed how antagonists prevent receptor activation and evaluated the inhibition strength of vorapaxar (a PAR1 antagonist) to block the native ligand bound to PAR1. 56 They observed that vorapaxar raised the G bu of native ligand binding by ∼2.84 kcal mol −1 and lowered the binding affinity.…”
Section: Drug Discovery and Verification Using Afmmentioning
confidence: 99%
“…In a further study, a series of cynarin derivatives was evaluated using this method, and results showed that one of the derivatives, Cyn-1324, reached a blocking effect of 31%. 96 In another study, the authors detailed how antagonists prevent receptor activation and evaluated the inhibition strength of vorapaxar (a PAR1 antagonist) to block the native ligand bound to PAR1. 56 They observed that vorapaxar raised the G bu of native ligand binding by ∼2.84 kcal mol −1 and lowered the binding affinity.…”
Section: Drug Discovery and Verification Using Afmmentioning
confidence: 99%
“…Chlorogenic acid derivatives C4 ( a – h ) were synthesized by following the procedure given in Scheme 1 [5355]. Evaluation of structure of novel derivatives was confirmed by spectroscopic methods such as IR, 1 H NMR, 13 CNMR and elemental analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction mixture was stirred at room temperature for 1–2 h. Solvent was removed under reduced pressure. The residue HCl was removed by adding EtOEt (20 × 3 mL) under vacuum [5355]. The residue collected was further dried and product was obtained in good yields.…”
Section: Methodsmentioning
confidence: 99%